2012
DOI: 10.1007/s11192-012-0645-5
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian scientific production in science education

Abstract: In the present study we analyzed the Brazilian scientific production in the area of science education. The study was structured on: data by research groups registered in Conselho Nacional de Desenvolvimento Científico e Tecnológico; analysis of the postgraduate strictu sensu programs; analysis of theses and dissertations linked to post-graduate programs; and papers in international databases. Our research was conducted strictly via world wide web, from December 2009 to September 2010. It was found that both nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
(20 reference statements)
0
11
0
11
Order By: Relevance
“…The initial milestones of public investment in science were the establishment of agencies such as the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Brazilian National Council for Scientific and Technological Development (CNPq) in the fifties [ 1 ] which give financial support and offer incentives to Brazilian post-graduate programs. Owing to the expansion and decentralization policies of the nineties, there was a significant growth of academic research output in the country [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial milestones of public investment in science were the establishment of agencies such as the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Brazilian National Council for Scientific and Technological Development (CNPq) in the fifties [ 1 ] which give financial support and offer incentives to Brazilian post-graduate programs. Owing to the expansion and decentralization policies of the nineties, there was a significant growth of academic research output in the country [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for the growth in INPA's scientific productivity is the presence of consolidated graduate programs that promote the contribution of and interactions with a greater number of students and post-doctoral fellows. Several studies have shown that there is a linear relationship between the number of graduate students and the number of scientific publications in Brazil (Guimarães 2004;De Meis et al 2007;Coutinho et al 2012). In fact, during the period studied, graduate students have been the main source of INPA first authorship in publications co-authored by permanent INPA staff researchers acting as thesis advisors.…”
Section: Amazonicamentioning
confidence: 99%
“…There was a significant increase in the number of papers published from 2014 which, in turn, reflects the increase in research groups in the area as shown by Coutinho et al . . According to the database of the Brazilian National Council for Scientific and Technological Development (CNPq), there was an increase in 113% in the number of research groups acting in Science Education from 2000 to 2010 and many of these groups focus in Biochemistry Education.…”
Section: Final Remarksmentioning
confidence: 99%
“…These authors also showed that the graduate programs-both MSc and PhD programs-in the area increased 310% in the decade 2001-2010. The highest number of research groups and graduation programs in Science Education are located in São Paulo [22] which is in accordance to our results of the State contribution to JBE.…”
Section: Final Remarksmentioning
confidence: 99%